2001
DOI: 10.1177/108056990106400204
|View full text |Cite
|
Sign up to set email alerts
|

Instructor and Student Perceptions of What is Learned by Writing the Business Report

Abstract: In many business communication courses students must write a business report.This study compared what business communication instructors believe their students learn and what writing skills they improve by completing the assignment with what students believe they learn and what writing skills they believe are improved. Data were gathered from members of the Association for Business Communication and from students who have completed a business report. Instructors see greater improvement in student writing skill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…These findings are important not only to the business communication discipline but also to other business disciplines. The finding of the short-term positive effect of the business communication course is consistent with the findings of other large-scale assessment studies of business communication education (e.g., Hiemstra, 2001;Murranka & Lynch, 1999). All of these studies have identified similar positive outcomes of business communication education right after students completed the course.…”
Section: Summary and Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These findings are important not only to the business communication discipline but also to other business disciplines. The finding of the short-term positive effect of the business communication course is consistent with the findings of other large-scale assessment studies of business communication education (e.g., Hiemstra, 2001;Murranka & Lynch, 1999). All of these studies have identified similar positive outcomes of business communication education right after students completed the course.…”
Section: Summary and Discussionsupporting
confidence: 88%
“…Several course-assessment studies report that students improve their skills in business communication by taking the course. For example, Hiemstra (2001) surveyed 286 business communication instructors and 406 students in the United States. The survey found that most instructors and students either agreed or strongly agreed that students improved in the areas of report organization, clarity, completeness, correctness, conciseness, content, grammar and mechanics, tone, audience analysis, and confidence in writing after completing the course.…”
mentioning
confidence: 99%
“…Communication is a critical component of business education (Arnett, McKendree, Fritz, & Roberts, 2008;Hiemstra, 2001;Russ, 2009;Zhao & Alexander, 2004). Research suggests that proficiency in written and oral communication is a necessity for an undergraduate business degree (Knight, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…communication courses (e.g., Grant, 2004;McPherson, 1998;Reinsch & Shelby, 1997;Rubin, 1996;Vogt, Atwong, & Fuller, 2005). What are the fundamental concepts that students must grasp to succeed in not only the class but the world (including Hiemstra, 2001;Netzley, 1999;Sensenbaugh, 1993;Wardrope & Bayless, 1999)? What concepts are the most troublesome for students to grasp, concepts that if not understood hold students back from greater learning in the course?…”
mentioning
confidence: 99%